THE RIGHT TO BE FORGOTTEN IN INDIA: COMPATIBILITY WITH PART-III OF THE CONSTITUTION - Upadhyay, Parth; Verma, Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the evolving concept of the "Right to be Forgotten" (RTBF) in India, analysing its legal basis and its maintainability within the framework of Part III of the Indian Constitution. While not explicitly recognized as a standalone right, the RTBF finds its roots in the right to privacy, declared a fundamental right under Article 21 through the Puttaswamy judgment. This right to informational privacy forms the cornerstone of the RTBF, empowering individuals to control their online narrative by limiting the accessibility of outdated or irrelevant personal information. However, the RTBF presents a complex constitutional challenge, as it must be balanced against the freedom of speech and expression guaranteed by Article 19(1)(a), as well as the public’s right to information. This paper explores the inherent tension between these competing rights, analysing how Indian courts have navigated this delicate balance in various RTBF cases. It examines the role of the Digital Personal Data Protection Act, 2023, in providing a legal framework for data protection and incorporating elements of the RTBF. The research delves into the challenges of implementing the RTBF in India, considering the vastness of the digital space, the role of intermediaries, and the need for clear guidelines regarding data erasure. Furthermore, the paper analyses the criteria for balancing individual privacy with freedom of expression and the public interest, emphasizing the importance of judicial interpretation and evolving jurisprudence in shaping the future of the RTBF in India. It concludes by offering suggestions for strengthening the RTBF framework, emphasizing the need for clearer legislation, standardized procedures, enhanced judicial guidance, and public awareness campaigns to ensure its effective implementation while safeguarding fundamental freedoms.